Determinant of financial distress in construction sub-sector companies in Indonesia and Malaysia - Putri, Trisandi Eka; Putri, Syifa Ariella (Proceeding International Conference on Accounting and Finance, 2024)
Financial distress is a company condition that shows a stage of decline or unhealthy in the company’s finances that occurred before bankruptcy or liquidation. Factors that are suspected to indicate that the company will experience financial distress are liquidity, leverage, company size, and net profit growth. So this study aims to determine the effect of liquidity, leverage, company size, and net profit growth on financial distress.The population in this study used construction sub-sector companies listed on the Indonesia Stock Exchange and Malaysia Stock Exchange in 2020-2022. This study used secondary data from annual financial statements listed on the Indonesia Stock Exchange and Malaysia Stock Exchange. This type of research is a quantitative type. The sampling method in this study used purposive sampling techniques. The data analysis technique in this study used multiple regression analysis.The results of this study show that partially the variables of liquidity and net profit growth have a negative effect on financial distress. While variable leverage positively affects financial distress. In addition, the variable size of the company has no effect on financial distress. The results also show that simultaneously the variables of liquidity, leverage, company size, and net profit growth affect financial distress.